FUNGSI HUKUM KETENAGAKERJAAN DALAM MENUJU PROSES INDUSTRIALISASI - Edi Krisharyanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
The Labour Act is a species and genus of law in general. It is covered every stage of regulation for an employee just before he start the job, during the job; within and after business relationship. Accordingly, the preparation of rule instruments should be well taken place in order to give the normative base in a frame of industrialization process.